2021
DOI: 10.1038/s41598-021-94414-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between central non-dipping pattern and platelet morphology in adults with type 1 diabetes without cardiovascular disease: a cross-sectional study

Abstract: The non-dipping pattern is nighttime systolic blood pressure (SBP) fall of less than 10%. Several studies showed that the non-dipping pattern, increased mean platelet volume (MPV), and platelet distribution width (PDW) are associated with elevated cardiovascular risk. Hypertensives with the non-dipping pattern have higher MPV than the dippers but this relationship was never investigated among people with type 1 diabetes mellitus (T1DM). This study aimed to investigate the association between the central dippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…These changes can be reversed by melatonin [ 57 , 58 ], highlighting the importance of pineal melatonin in the circadian optimization of pancreatic β-cell function. Circadian dysregulation is also intimately linked to a diverse array of T1DM symptomatology [ 59 ], including nocturnal non-dipping blood pressure increasing kidney disease [ 60 ], cardiac autonomic neuropathy [ 61 ], platelet morphology [ 62 ], microvascular complications [ 63 ], and patterned immune activity [ 64 ], whilst circadian variation in basal insulin requirement can be an early marker of autoimmune polyendocrine syndromes in T1DM [ 65 ]. Such data highlight the role of alterations in the circadian rhythm in T1DM pathophysiology.…”
Section: Wider T1dm Pathophysiologymentioning
confidence: 99%
“…These changes can be reversed by melatonin [ 57 , 58 ], highlighting the importance of pineal melatonin in the circadian optimization of pancreatic β-cell function. Circadian dysregulation is also intimately linked to a diverse array of T1DM symptomatology [ 59 ], including nocturnal non-dipping blood pressure increasing kidney disease [ 60 ], cardiac autonomic neuropathy [ 61 ], platelet morphology [ 62 ], microvascular complications [ 63 ], and patterned immune activity [ 64 ], whilst circadian variation in basal insulin requirement can be an early marker of autoimmune polyendocrine syndromes in T1DM [ 65 ]. Such data highlight the role of alterations in the circadian rhythm in T1DM pathophysiology.…”
Section: Wider T1dm Pathophysiologymentioning
confidence: 99%
“…The activation and aggregation of platelets are potential factors contributing to the increased risk of thrombosis in patients with hypertension (16)(17)(18). Some studies have indicated a potential correlation between MPV and blood pressure (19,20). However, despite these investigations conducted, the current clinical evidence regarding the association between PIs and stroke remains inconclusive and lacks longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%